FREQUENCY OF ANGIOGRAPHICALLY SIGNIFICANT CORONARY ARTERY DISEASE IN PATIENTS UNDERGOING VALVE REPLACEMENT SURGERY WITH OR WITHOUT RISK FACTORS FOR ATHEROSCLEROSIS - Shabeer, Hassan; Nawaz, Ali; Tuyyab, Farhan; Khattak, Tariq Hussain; Khadim, Rehana; Shafique, Hafiz Muhammad; Chaudhry, Azhar Ali (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of angiographically significant coronary artery disease in patients undergoing valve replacement surgery with or without risk factors for atherosclerosis.Study Design: A single center, descriptive cross-sectional study.Place and Duration of Study: Adult Cardiology department of AFIC & NIHD from 1st Jan 2017 to 30th Jun 2017.Material and Methods: All consecutive patients who underwent coronary angiography before valve replacement/repair surgery were included in the study. Excluded Patients were those who had previous valve surgery, known CAD, post CABG and Post PCI patients, associated risk factors like diabetes, hypertension, dyslipidemia, family history of coronary artery disease, smoking and BMI of the patients were recorded. All the information was entered in an annexed pro-forma. All the collected data was entered and analyzed using the SPSS-23.Results: A total of 136 patients underwent coronary angiography before valve replacement/repair surgery during study period and were recruited. Mean Age of the patients was 48.23 ± 5.2 years with minimum age 31 years and maximum 67 years. There were 80 (58.8%) male patients while 56 (41.2%) female patients. Smoking was found to be the most prevalent risk factor 98 (72.1%) followed by family history 67 (49.3%), hypertension 65 (48.0%), Obesity (BMI≥ 30) 63 (46.3%), diabetes mellitus 42 (30.9%) and dyslipidemia 35 (25.7%). Out of total patients, 63 (46.3%) patients had significant CAD. 33 (24.3%) had AVR, 89 (65.4%) patients had MVR while 14 (10.3%) patient had DVR.Conclusion: Our study shows that significant proportion of patients above 40 years of age have asymptomatic underlying CAD (46%), this frequency of angiographically significant CAD in our patient population signifies pre valve replacement screening by coronary angiogram so that coronary bypass grafting can be offered to those patients concomitantly with valve replacement.